Effect of different extraction techniques on yield and quality of essential oils from rhizomes of Cyperus Rotundus - Azhari, H. Nour; Majda, A. Ali; Mwadda, A. Sharef; Lina, O. Elbadri; Fatima, A. Ahmed; Nour, A. H.; Mohammed, Sulieman (2018)
Medicinal plants play an important role as useful resources in producing new and safer drugs for the treatment of various diseases. The objective of this study was to compare the yield, chemical composition and antimicrobial activity of essential oils (EOs) obtained by two different techniques from rhizomes of genius Cyperus of which C. rotundus (Family: Cyperaceae) belongs to. The EOs was obtained by Steam Distillation (SD) and Hydrodistillation (HD). The chemical compositions were analyzed by Gas Chromatography-Mass Spectroscopy (GC-MS). The antimicrobial activity was tested by disc diffusion method against four microbes namely; Escherichia coli, Klebsiella pneumoniae, Staphylococcus aureus and Candida albicans. The oil content was 0.18% and 0.27% (v/w) for HD and SD, respectively. The GC-MS analysis led to identification of 71 and 74 components, respectively. The dominant compounds for HD were: 3-Hydroxy-2-(2-methylcyclohex-1-enyl) propionaldehyde (11.20%); 2-cyclohexene-1-1one, 3-methyl-6(1-methyl-31) (8.23%) and 1,4-methanoazulene-9-methanol (5.43%). Whereas for SD were: 3-Hydroxy-2-(2-methylcyclohex-1enyl) propionaldehyde (12.94%), Tricyclo [6.3.0.0(2,4) undec-8ene,3,3,7,11-tetramethyl-(6,48%), 1-Oxaspiro[2.5]octane,5,5-dimethyl-4-(3-methyl-1,3-butan dienyl)- (5.66%) and 4,8,13-Cyclotetradecatriene-1,3-diol,1,5,9-diol,1,5,9-trimethyl-12-(1-methylethyl) -(5.57%). The antimicrobial activities of the oils against tested microorganism were extremely broad, the inhibition zones ranged between 10 and 17 mm. For HD oil, the Candida was the most sensitive to the oil (16 mm) and S. aureus was the most resistant (10 mm). Whereas, for SD oil, the S. aureus was the most sensitive (17 mm) while K. pneumoniae and C. albicans were the most resistance (12 mm). In conclusion, the results obtained from this study proved that the extraction technique is one of the main factors that can affect in the EOs yield, constituents and biological activities. Moreover, the results suggest that the EOs of C. rotundus could be a potential source of antimicrobial ingredients for food and pharmaceutical industries. Therefore, a wide bioassay against more microbes, isolation and identification of bioactive compounds would be an interesting line of inquiry for the further studies.